Sensitivity analysis of leaching process on rare earth elements by using metsim software - Wan Hanisah, Wan Ibrahim; F. N., Yahya; Ruwaida, Abdul Rasid; A., Hisham; L. N., M. Suli (2018)
Leaching is part of the hydrometallurgical treatment in the separation of rare earth elements (REEs). The increase of demand for REEs in the world but its limited supply caused by the separation process that has negative environmental impact, as well as high costs of laboratory work, the alternative method to study on the extraction of these resources are urgently needed. This can be done through simulation study that eliminates the number of experiment that needs to be carried out. In this work, a sensitivity analysis of the leaching process for light rare earth elements (LREEs); Lanthanum (La) and Neodymium (Nd) from monazite concentrate was carried out by employing a software called METSIM which is able to model metallurgical processes. METSIM software is also able to calculate mass and heat balance of complicated hydrometallurgy processes and furthermore, its function has been expanded to involved chemical reactions, process control and equipment sizing. The simulation of the digestion and the leaching process was run and compared with experimental work from the literature, which aimed to optimize the leaching process. Leaching is an extraction process of a substance from a solid material that is dissolved in a liquid. In this study, the leaching process is modelled as a two-steps process, in which the first step is the digestion process, followed by the actual leaching process. The monazite concentrate is made strong bonds as REEs oxide, therefore, they are not soluble in water before leaching process. For the digestion process, the monazite concentrate was mixed with sulfuric acid (H2SO4) in the digestion reactor. The precipitates which contain leachate was then mixed with deionised water in the leaching reactor to increase the solubility of La and Nd. The reaction equations for the digestion reactor are as shown in Equations (1) and (2), while for the leaching reactor are shown by Equations (3) and (4) as follows: